Income inequality and External Wealth of Nations - Carrera, Jorge (2024)
We study the relationship between income inequality and external wealth using dynamic panel data models with 5-years average observations to consider the slow motion of available data in the case of 88 emerging and developing economies for the period 1970–2020. We find evidence of a significant positive association between inequality indicators and net external wealth. This relationship is statistically significant for all income inequality measures and net external wealth variables. If the Top 1 of the richest individuals in a given country increments their share by 1 % point this will produce an average same-year increment in net foreign assets of 0.45 % in terms of the country’s GDP. The long-run effect is more than double in magnitude (1.05 % of GDP). For the Top 10, the long-run effect increases tenfold (11.6 % of GDP). When disaggregated into foreign assets and liabilities, we find a heterogeneous behavior of the financial elites. These findings reveal that financialized elites have a greater propensity to accumulate external wealth than the rest of the population.